Adipokines and inflammation: is it a question of weight?. (10th April 2018) - Francisco, Vera; Pino, Jesus; Gonzalez‐Gay, Miguel Angel; Mera, Antonio; Lago, Francisca; Gómez, Rodolfo; Mobasheri, Ali; Gualillo, Oreste
Abstract : Obesity has reached epidemic proportions in the Western society and is increasing in the developing world. It is considered as one of the major contributors to the global burden of disability and chronic diseases, including autoimmune, inflammatory and degenerative diseases. Research conducted on obesity and its complications over the last two decades has transformed the outdated concept of white adipose tissue (WAT) merely serving as an energy depot. WAT is now recognized as an active and inflammatory organ capable of producing a wide variety of factors known as adipokines. These molecules participate through endocrine, paracrine, autocrine or juxtacrine crosstalk mechanisms in a great variety of physiological or pathophysiological processes, regulating food intake, insulin sensitivity, immunity and inflammation. Although initially restricted to metabolic activities (regulation of glucose and lipid metabolism), adipokines currently represent a new family of proteins that can be considered key players in the complex network of soluble mediators involved in the pathophysiology of immune/inflammatory diseases. However, the complexity of the adipokine network in the pathogenesis and progression of inflammatory diseases has posed, since the beginning, the important question of whether it may be possible to target the mechanism(s) by which adipokines contribute to disease selectively without suppressing their physiological functions. Here, we explore in depth the most recent findings concerning the involvement of adipokines in inflammation and immune responses, in particular in rheumatic, inflammatory and degenerative diseases. We also highlight several possible strategies for therapeutic development and propose that adipokines and their signalling pathways may represent innovative therapeutic strategies for inflammatory disorders.